Konseling Individu dengan Teknik Cognitive Restructuring untuk Meningkatkan Self Acceptance pada Remaja - Cindi Monica; Abdur Razzaq; Zhila Jannati (Scidacplus, 2024)
This study analyzes Individual Counseling with Cognitive Restructuring techniques to increase Self-Acceptance in Adolescents in Prabumulih City (Case Studies in Foreign Clients Who Experience Pregnancy Out of Wedlock), the background for efforts to provide individual counseling guidance through Cognitive Restructuring techniques to LN clients facing conditions outside of marriage marriage which is a disgrace to clients in the community, thus causing LN clients to experience a decline (self-acceptance) which has signs starting from giving up on circumstances, having difficulty accepting oneself, swallowing bitterness from past conditions which have an impact on one's current life. The purpose of the study was to describe the level of self-acceptance of adolescents in Prabumulih City before applying individual counseling with cognitive restructuring techniques, the factors that influence the low self-acceptance of foreign clients, the implementation of individual counseling with cognitive restructuring techniques to overcome self-acceptance and to find out the description of the level of self-acceptance in clients after applying cognitive restructuring techniques. The approach used in this research is qualitative. The research subjects are LN clients. Data collection techniques through observation, interviews and documentation. The results of the study show: First, an overview of the level of self-acceptance before it is implemented, namely foreign clients cannot accept themselves and make the opinions of others a burden on their minds, foreign clients feel ashamed, hopeless, regretful and unsure of their own abilities. Second, the factors that affect low self-acceptance are foreign clients who do not prioritize honesty, receive unfair treatment from the surrounding community or support from those closest to them. Third, the implementation of counseling which is carried out using three stages, both at the beginning of counseling, the work stage and the action that seeks to go through each step of implementing rational therapy, identification, knowing the extent of the therapeutic steps that have been carried out in achieving recognition and coping thought (CT) exercises, moving from thoughts negative to coping thought (CT), recognition and positive reinforcement exercises. Fourth, an overview of the level of self-acceptance after individual counseling with cognitive restructuring techniques is applied, in which LN clients provide confidence in themselves with compassion or genuinely improve themselves to become better persons and focus on taking care of their husbands and children without worrying about the response of society.